Real Trade Costs, Fragmentation and Employment - Kurt Kratena; Michael Wüger (Austrian Institute of Economic Research (WIFO), 2001)
This paper attempts to quantify the impact of fragmentation on employment. Factor demand functions for labour and intermediates and mark up price equations derived from a Generalized Leontief cost function at industry level are estimated. Import prices and output prices influence the price of intermediates via a technology matrix from input - output tables. A decrease in import prices (real trade costs) has a twofold impact on labour demand: (i) substitution of domestic employment by partly imported intermediates (= outsourcing or fragmentation) (ii) increased employment due to higher demand caused by an increase in price competitiveness.
Keywords: F11; F15; D20; 330; fragmentation; outsourcing; real trade costs; Generalized Leontief cost functions; Außenwirtschaftstheorie; Outsourcing; Internationale Arbeitsteilung; Erwerbstätigkeit; Schätzung